Persepsi Siswa terhadap Quality of School Life pada Sekolah yang Pernah Mengalami Kondisi Rusak Fisik (Studi Kasus pada SDN X di Jakarta) - Grace Paskahlisa Dorothy; Monika Monika; Erik Wijaya (Fakultas Psikologi Universitas Tarumanagara, 2018)
Students' perception of school is an important factor in student development in school. This study aims to determine the description of quality of school life of students SDN X in Jakarta. the physical condition of the school that previously suffered total physical damage such as unfit for use, until it undergoes a total renovation and can be reused. The physical condition of the school affects the students' perception of the quality of the students in their school. Quality of school life is a positive or negative experience and other feelings related to the dimensions of school life, in general and in particular. It is the main indicators of the quality of school life for students, to the satisfaction and dissatisfaction, associated with the dimension and results. Research method used is mix method. The subjects of this study are the students of grade IV to VI in SDN X Jakarta amounting to 124 students who distributed questionnaires and 4 students to be interviewed. From the results of quantitative research can be concluded that the picture of quality of school life in SDN X Jakarta tends to be high and students' perceptions of the condition of schools that have been renovated more positive than schools that are still in physical damage, especially in dimensions general satisfaction, negative feelings, and achievement. Based on these results that the physical condition of the school affects students' perceptions of school and student achievement in school. Key words: Quality of school life, primary school, dimension of QSL